Prevalence of water pipe smoking and associated risk factors among female adolescents - Saeed Bashirian; Majid Barati; Manoochehr Karami; Behrooz Hamzeh; Elahe Ezati (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The prevalence of water pipe smoking is increasing among young people, but there are limited data on its use among adolescents in Iran. The aim of this study is to investigate the prevalence of WP smoking and associated risk factors among female adolescents in Western Iran. MATERIALS AND METHODS: This cross-sectional study was conducted in schools. It included 1302 middle school (48.1%) and high school (51.9%) female students (grades 7-12) recruited through stage random sampling and conducted in 2019 in the western city of Kermanshah, Iran. The data collection tool was a researcher-made questionnaire. Logistic regression analyses and descriptive statistics were executed using SPSS version 22. RESULTS: The mean (standard deviation) ages of the students and the ages when the participants started WP smoking were 15.22 ± 1.85 and 13.64 (1.64), respectively. Nearly 32.2% had a single experience of WP smoking during their lifetime and 20.4% were current consumers of WP. Most of the subjects smoked WPs at their friends' home (45.8%) and with their friends (47.4%). The significantly important factors that affect WP smoking in these age groups are the father's and mother's occupation, family size, living with others, father's education, having a friend who smokes WPs, friends' encouragement to smoke WP, and being in a family that smoke WPs. CONCLUSIONS: Considering the increasing popularity of WP among adolescent females and its increasing prevalence, the results showed that Water pipe smoking with friends played a key role in WP smoking among female adolescents. There is a need to design interventional studies to increase people's skills and to design and implement programs to prevent water pipe.